Method for the Analysis of Cannabinoids and Terpenes in Cannabis. (27th November 2019) - Giese, Matthew W; Lewis, Mark A; Giese, Laura; Smith, Kevin M
Abstract: The requirements for an acceptable cannabis assay have changed dramatically over the years resulting in a large number of laboratories using a diverse array of analytical methodologies that have not been properly validated. Due to the lack of sufficiently validated methods, we conducted a single- laboratory validation study for the determination of cannabinoids and terpenes in a variety of commonly occurring cultivars. The procedure involves high- throughput homogenization to prepare sample extract, which is then profiled for cannabinoids and terpenes by HPLC-diode array detector and GC-flame ionization detector, respectively. Spike recovery studies for terpenes in the range of 0.03–1.5% were carried out with analytical standards, while recovery studies for Δ 9 -tetrahydrocannabinolic acid, cannabidiolic acid, Δ 9 -tetrahydrocannabivarinic acid, and cannabigerolic acid and their neutral counterparts in the range of 0.3–35% were carried out using cannabis extracts. In general, accuracy at all levels was within 5%, and RSDs were less than 3%. The interday and intraday repeatabilities of the procedure were evaluated with five different cultivars of varying chemotype, again resulting in acceptable RSDs. As an example of the application of this assay, it was used to illustrate the variability seen in cannabis coming from very advanced indoor cultivation operations.